A TEXT ANALYSIS ON PRESIDENT JOKO WIDODO’S SPEECH AT APEC CEO SUMMIT ASIAN PACIFIC - Ahmad Madkur (Jurnal Pedagogy, 2018)
According to Van Dijk, there are three dimensions of discourse analysis, namely text, social cognition and social context. This study was focused on the first dimension, text. Joko Widodo’s first presidential English speech on economic issues in front of international audience in CEO Summit in Beijing was one of speeches a lot of people talk about. Some like while some others dislike. This study was intended to analyze the transcript of the speech. This text analysis was based on Van Dijk’s design in which the unit elements of the analysis are divided into three parts: macro-structure, suprastructure and microstructure. The result of the analysis revealed that in macrostructure element, several sentences in the presidential speech were less coherent in term of stating theme. Then, in suprastructure, the scheme of the speech consisted of opening, content and closing. Finally, in the microstrucure, the semantic aspect could be found in setting, detail, intention, presupposition, and normalization.